Memanfaatkan Lahan Kosong Di Pekarangan Rumah Guna Menambah Pendapatan Ekonomi Rumah Tangga - Afnina Afnina; Baniara Baniara; Rauzatul Jannah (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Problems that occur where there is an addition to the cost of living while income is fixed, the presence of vacant land in the yard of the house that is not used optimally, and the lack of socialization and motivation for the utilization of vacant land for the residents of Matang Seulimeng Village. In this regard, the purpose of this community service is to assist the community in delivering financial management messages in the health sector, especially regarding efforts to utilize vacant land in the yard of the house to increase household economic income. The research method is through financial management counseling in the health sector. The results of this community service show that people are starting to become aware of managing household finances because of the addition of living costs during pandemic conditions while income does not increase. Increased knowledge of the community in utilizing vacant land by planting vegetables, flowers that can be sold, raising poultry, fish, and so on so that it can increase household economic income as well as guarantee healthy food because plants and livestock are far from the use of fertilizers or pesticides.